Molecular Cloning and Phenotypic Analysis of Drug-resistance Mutants with Relevant S-region Variants of HBV for a Patient during 189-month Anti-HBV Treatment. Issue 4 (May 2019) - Liu, Yan; Wu, Chunchen; Chen, Rongjuan; Li, Xiaodong; Xu, Zhihui; Li, Qi; Li, Le; Wang, Fu-Sheng; Yang, Dongliang; Lu, Mengji; Xu, Dongping
Background: A unique chronic hepatitis B patient was followed over 189 months of nucleoside/nucleotide analogue (NA) therapies with the analysis of multiple drug-resistance HBV mutants. Methods: Clonal sequencing (≥20 clones/sample) was performed on sera sampled at 41 time points, and the phenotypic features of eight representative mutants were analysed. Results: Lamivudine (LAM)-, adefovir dipivoxil (ADV)-, entecavir (ETV)- and repeat ADV-resistance mutants emerged upon individual sequential NA monotherapy. The efficacy of NA combination rescue therapies ranked as LAM+ADV < ETV+ADV < ETV+ tenofovir disoproxil fumarate (TDF). Specifically, LAM+ADV and ETV+ADV suppressed viral loads to <100 IU/ml for a long period of time, either with or without late stage HBV DNA fluctuations. Furthermore, ETV+TDF suppressed the viral load to <10 IU/ml. During the LAM+ADV and ETV+ADV combination therapies, ETV-resistance mutants dominated at most time points, and multidrug-resistance (MDR) mutants that harboured LAM-, ETV- and ADV-resistance mutations were intermittently detected. Interestingly, the rtA181T-causative sW172stop to sW172non-stop mutation transition was observed at HBV DNA fluctuations. In a phenotypic analysis, two MDR strains had cross-resistance to LAM, ETV and ADV, and a lower susceptibility to TDF (<10-fold decrease compared with the wild-type strain). In contrast, the natural replication capacity was inversely associated with the number of primary resistant mutations which would limit MDR mutant development. Conclusions: Taken together, viral drug susceptibility, replication capacity, and perhaps immunological adaptation may play coordinated roles in the fitness of drug-resistance mutants. ETV+TDF therapy is the preferred option for treating chronic hepatitis B patients with multiple drug failure.